Impact of some environmental factors on the temporal variability of pink and white shrimps postlarvae in Terminos Lagoon, Southern Gulf of Mexico (Revista de Biología Marina y Oceanografía, 2024)
The pink shrimp Farfantepenaeus duorarum and white shrimp Litopenaeus setiferus are species of high ecological and commercial value, therefore, studies that analyze their temporal variability and their relationship with the physical ambient in the long term becomes necessary. The aim of this is study was to assess the impact of some environmental factors on the temporal variability of the postlarvae of both species in Terminos Lagoon, Southern Gulf of Mexico, a region recognized for being the refuge, breeding and feeding habitat for these species. Organisms were collected at three different depths (1.5, 4 and 9 m) using a multiple net system (trapezium-type nets, 50 cm of mouth diameter, 1.5 m in length, and mesh size of 505 mm) in a fixed location at the junction between the lagoon and the open waters of the Gulf of Mexico during nocturnal sampling expeditions executed from May 2010 to September 2013. In each sampling expedition, hydrographic data (e.g., temperature, salinity) were recorder using a multiparameter sonde, meteorological data (e.g., precipitation, wind velocity) were acquired from a local meteorological station, while the surface circulation pattern was obtained from a numerical model. The results showed changes in the environmental factors, with highest precipitation (250 mm) in 2010. The surface temperature revealed values of ~30 ºC with slight variations throughout the study period. Salinity showed minimum values (< 30) in the seasons of highest precipitation, increasing during the dry season with values of > 33. Strong currents (> 0.25 m s-1) in a north to south direction that reached the coast and then the interior of the lagoon were observed in specific dates. Mesoscale anticyclonic eddies (with a diameter of ~30 km) were also observed in the southern gulf. High density values of both species were observed, reaching 33,619 ind 100 m-3 for L. setiferus, and 57,948 ind 100 m-3 for F. duorarum. Peaks were associated when strong surface currents were observed reaching the interior of the lagoon, which was confirmed from multivariate statistical techniques. The results presented here contribute to the understanding of the role that some environmental factors exert on the density of two species with high, both economic and ecological, value in the Terminos Lagoon, which is of critical relevance in regions recognized for their high biological diversity.